Effect of storage time and packaging system on minimally processed green pepper (Capsicum annuum) - Natalí López-Mejía; Luis Eduardo Ordóñez-Santos (TecnoLógicas, 2018)
Green peppers, a Solanaceaecultivated in tropical zones, are used as natural food coloring and flavoring. Considered perishable vegetables, they are usually stored between 7.5 and 8° C in order to avoid accelerating fruit transpiration and cold damage (chilling injury), which in turn affect their characteristic green coloration. At present, there are no studies available on the degradation of pigments in Minimally Processed Pepper (MPP). Therefore, the objective of this study was to evaluate the effect of two packaging systems and storage time on the physicochemical characteristics of MPP. For this purpose, the fruits were stored without packaging (control group), in high-density polyethylene (HDPE), and in high-density polyethylene with a vacuum seal (HDPE-V) under refrigeration conditions (9° C and 45% RH). The variables weight loss, pH, titratable acidity, total chlorophyll concentration, and total carotenoids were evaluated on days 0, 7 and 14 of storage. The results indicate that both packaging system and storage time had a significant effect on the quality characteristics of MPP. After 14 days of storage, the green pepper fruits packed in HDPE-V presented a retention of 62% of the chlorophylls, 75% of the total carotenoids, and less color change (ΔE = 12) with respect to time to storage time 0.Based on these results, it can be concluded that the HDPE-V container can be a suitable alternative to preserve MPP.